2013
DOI: 10.1007/s12560-013-9104-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Poliovirus Concentration and Recovery from Treated Wastewater by Two Electropositive Filter Methods

Abstract: Enteric viruses are often present in low numbers in various water matrices. Virus sampling therefore involves multiple concentration steps to condense large samples down to small volumes for detection by cell culture or molecular assays. The NanoCeram® Virus Sampler has been demonstrated to be effective for the recovery of viruses from tap water, surface waters, and seawater. The goal of this study was to evaluate a new method using NanoCeram® filters for the recovery of poliovirus 1 (PV-1) from treated wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…ViroCap and NanoCeram filters have been examined for their ability to concentrate viruses and bacteriophage from water, including adenovirus (Gibbons et al 2010 ), bacteriophage MS2 (Bennett et al 2010 ; Gibbons et al 2010 ; Ikner et al 2011 ), coxsackievirus B5 (Ikner et al 2011 ; Karim et al 2009 ), echovirus 1 (Ikner et al 2011 ), echovirus 7 (Karim et al 2009 ), norovirus (Karim et al 2009 ), and poliovirus (Bennett et al 2010 ; Fagnant et al 2014 ; Ikner et al 2011 ; Karim et al 2009 ). Viral recovery rates with ViroCap and NanoCeram filters are generally similar to or better than the recovery rates obtained using other electropositive filters, such as glass wool and 1 MDS filters (Bennett et al 2010 ; Fagnant et al 2014 ; Karim et al 2009 ; Soto-Beltran et al 2013 ). Finally, ViroCap filters are also economical, easy to use, and field deployable (Cashdollar and Wymer 2013 ; Fagnant et al 2014 ; Fagnant et al 2017b ).…”
Section: Introductionsupporting
confidence: 51%
“…ViroCap and NanoCeram filters have been examined for their ability to concentrate viruses and bacteriophage from water, including adenovirus (Gibbons et al 2010 ), bacteriophage MS2 (Bennett et al 2010 ; Gibbons et al 2010 ; Ikner et al 2011 ), coxsackievirus B5 (Ikner et al 2011 ; Karim et al 2009 ), echovirus 1 (Ikner et al 2011 ), echovirus 7 (Karim et al 2009 ), norovirus (Karim et al 2009 ), and poliovirus (Bennett et al 2010 ; Fagnant et al 2014 ; Ikner et al 2011 ; Karim et al 2009 ). Viral recovery rates with ViroCap and NanoCeram filters are generally similar to or better than the recovery rates obtained using other electropositive filters, such as glass wool and 1 MDS filters (Bennett et al 2010 ; Fagnant et al 2014 ; Karim et al 2009 ; Soto-Beltran et al 2013 ). Finally, ViroCap filters are also economical, easy to use, and field deployable (Cashdollar and Wymer 2013 ; Fagnant et al 2014 ; Fagnant et al 2017b ).…”
Section: Introductionsupporting
confidence: 51%
“…VIRADEL method has been widely used for large volumes of sample to be processed, notably river samples ( Hamza et al, 2009 ; Maunula et al, 2012 ), tap water samples ( Hill et al, 2009 ; Polaczyk et al, 2007 ), groundwater samples ( Lee et al, 2011 ), and coastal waters ( Fong et al, 2005 ; Goyal and Gerba, 1983 ; Katayama et al, 2002 ). Wastewater sample volumes ranging from 0.5 to 400 L were used in recent studies that applied VIRADEL as primary concentration method ( Falman et al, 2019 ; Kuo et al, 2010 ; Masclaux et al, 2013 ; Osuolale and Okoh, 2017 ; Prado et al, 2011 ; Soto-Beltran et al, 2013 ). However, the processing of large volumes of samples leads to the concentration of PCR inhibitors.…”
Section: Methods Of Pre-treatment Of Wastewater Samplesmentioning
confidence: 99%
“…Research to date has typically focused on recovery of virus by modifying primary concentration (filters) steps, but little attention has been given to subsequent concentration procedures which could also influence virus recovery 18 . It has been demonstrated that different secondary concentration techniques can affect virus recoveries 6,13,19,20 .…”
Section: Discussionmentioning
confidence: 99%